Oil Price Risks - Bacon, Robert; Kojima, Masami (World Bank, Washington, DC, 2012)
Oil prices more than tripled between January 2004 and March 2008. The effects can be hard on countries with large net oil imports relative to income. This note sets out a measure of vulnerability to oil price shocks and breaks it down into its components. That allows cross-country benchmarking and helps to show how changes in such factors as energy efficiency and the real exchange rate can make countries more vulnerable or less so.